Modulation of Cell-associated Plasminogen Activation by Stromelysin-1 (MMP-3) - Ugwu, F.; Lemmens, G.; Collen, D.; Lijnen, H. R. (Thrombosis and Haemostasis, 1999)
Stromelysin-1 (MMP-3) cleaves a 55 kDa kringle 1-4 fragment, containing the lysine-binding site(s) involved in cellular binding, from 92 kDa plasminogen and removes a 17 kDa NH2-terminal fragment, containing the cellular receptor-binding site, from 45 kDa urokinase (u-PA), but a potential role of MMP-3 in the regulation of cellular fibrinolytic activity by affecting binding and/or activation of plasminogen and/or single-chain u-PA has not been established. Human plasminogen (input concentration 100 nM for 4 × 106 cells per ml) was shown to bind specifically to human monocytoid THP-1 cells, to murine MMP-3 deficient smooth muscle cells (SMC) and fibroblasts (1.9, 0.92 and 1.0 × 106 molecules per cell, respectively). Treatment with MMP-3 (final concentration 0-50 nM) of cells saturated with bound plasminogen (about 25 nM), overnight at 37° C, resulted in a dose-dependent reduction of the amount of u-PA activatible plasminogen (reduction to 25-40% of the value in the absence of MMP-3). Immunoblotting with specific monoclonal antibodies and autoradiography of eluates of the cells treated with MMP-3 revealed cleavage of plasminogen into the 55 kDa fragment and miniplasminogen (kringle 5 plus the proteinase domain).Binding of human single chain u-PA (scu-PA) to human THP-1 and HT 1080 cells amounted to 2.5 × 106and 7.1 × 106 molecules per cell, respectively. Treatment with MMP-3 (final concentration 0-25 nM) of cell-bound u-PA (about 17 nM for THP-1 and 47 nM for HT1080 cells), overnight at 37° C, did not alter cell-associated u-PA activity, measured in a direct chromogenic substrate assay or in a plasminogen-coupled chromogenic substrate assay (residual u-PA activity always ≥85% of that without MMP-3 treatment). Autoradiography of 125I-labeled u-PA moieties, removed from the cells by treatment with acid or with phosphatidylinositol phospholipase C, confirmed that u-PA remained essentially intact after MMP-3 treatment.These data indicate that MMP-3 may downregulate cell-associated plasmin activity by decreasing the amount of activatible plasminogen, without affecting cell-bound u-PA activity.